KARAKTERISTIK SOFT TISSUE TUMOR EKSTREMITAS BERDASARKAN TIME INTENSITY CURVE PADA DYNAMIC CONTRAST ENHANCEMENT - MRI - Putu Krisna Ariadi; Kadek Yuda Astina; Nyoman Supriyani (JRI (Jurnal Radiografer Indonesia), 2022)
ABSTRACT Background: Perfusion MRI such as Dynamic Contrast Enhancement (DCE) sequences are able to provide detailed structural and metabolic information about tumor tissue, so the diagnostic imaging results can approach histologic diagnosis non-invasively. The purpose of this study was to analyze the relationship between the Time intensity curve (TIC) and the characteristics of soft tissue tumors in the extremities, and also to determine the sensitivity and specificity values. Methods: This research is a descriptive quantitative study using retrospective data. The samples of this study were all patients with soft tissue tumors of the extremities who underwent MRI examination of the extremities at the RIR Installation of Prof. RSUP. Dr. IGNG Ngoerah Denpasar and histopathological examinations were implemented during the period of June 2021-July 2022. Types I-II were associated with benign tumors. Meanwhile, the type of III-V as malignant tumors were compared with the histopathological characteristics of soft tissue tumors. Results: From 30 samples, it was found the result of the spearman rank test was about the relationship between TIC and soft tissue tumor characteristics. It was shown that the p value was 0.014 (p<0.05), and the result of diagnostics test with a 2x2 table obtained a sensitivity value of 89.47% and a specificity of 9.09% Conclusion: Time intensity curve on DCE MRI is able to distinguish the characteristics of soft tissue tumors of the extremities, especially malignancies.